Role of Credit Risk in Performance difference between A and B Class Banks in Nepal - Risal, Hari Copal; Poudel, Suprima (NRB Economic Review, 2020)
This paper explains the performance differences between A and B class financial institutions arising from credit risk. The dynamic panel data from 2008 to 2019 has been considered from all 28 commercial banks and 11 national level development banks for analysis. Arellano Bond method has been performed to control the unobserved heterogeneity and to reduce biasness in the parameter estimation as they have both cross sectional and time dimensions. The results have shown clear differences in credit risk status between A class and B class bank with all the parameters except for Return on Assets (ROA). The results show that the A class commercial banks are less vulnerable than the B class bank as measured by Standard deviation of ROA (standard deviation of return on equity (SDROE) both, yet offer substantially higher ROE and fairly higher NIM. Findings suggest that the past performance BFIs, regardless their classes, are capable enough to predict their future performance as all lag variables are significant. Development banks are advised to focus on maintaining appropriate credit to deposit ratio (CDR) as it has been affecting most of the performance indicators whereas, commercial banks are advised to monitor their loan loss provision to total loans and advances (LLPTLA) for better performance. The control variables have been found to have negligible effect on performance of banks yet higher inflation deteriorates the performance even at a small amount. Further, contradictory findings on influence of real gross domestic product (GDP) growth with the performance demands a need of further research. To recapitulate, the credit risk plays a vital role in performance of banks in Nepal and A class banks safer with returns.